Chemical Composition of Fresh and Dried Penja Fish (Sicyopterus pugnans) - Muh Kasim; Ida Astuti; Darmawan Darmawan (Politeknik Negeri Sambas, 2025)
Sicyopterus pugnans, commonly known as Penja fish, is a freshwater endemic species with a savory taste and distinctive aroma, making it a popular food commodity in West Sulawesi, Indonesia. This fish is commonly consumed either fresh or dried. This study aimed to determine and compare the nutritional composition of Penja fish in fresh and dried forms. The study employed an experimental method using proximate analysis, which included measurements of protein, fat, ash, and moisture content. The samples consisted of fresh Sicyopterus pugnans and traditionally processed dried fish. The results showed that fresh Penja fish contained 17.98% protein, 3.62% fat, 1.55% ash, and 71.87% moisture. In contrast, dried Penja fish exhibited increased nutrient concentrations with 63.80% protein, 12.70% fat, 7.88% ash, and reduced moisture content of 12.54%. The study concludes that Penja fish is highly nutritious, particularly in protein content, and has significant potential to be developed as a high-nutrient local food source.